Galaxy Zoo: probabilistic morphology through Bayesian CNNs and active learning. Issue 2 (7th October 2019) - Walmsley, Mike; Smith, Lewis; Lintott, Chris; Gal, Yarin; Bamford, Steven; Dickinson, Hugh; Fortson, Lucy; Kruk, Sandor; Masters, Karen; Scarlata, Claudia; Simmons, Brooke; Smethurst, Rebecca; et al.
ABSTRACT: We use Bayesian convolutional neural networks and a novel generative model of Galaxy Zoo volunteer responses to infer posteriors for the visual morphology of galaxies. Bayesian CNN can learn from galaxy images with uncertain labels and then, for previously unlabelled galaxies, predict the probability of each possible label. Our posteriors are well-calibrated (e.g. for predicting bars, we achieve coverage errors of 11.8 per cent within a vote fraction deviation of 0.2) and hence are reliable for practical use. Further, using our posteriors, we apply the active learning strategy BALD to request volunteer responses for the subset of galaxies which, if labelled, would be most informative for training our network. We show that training our Bayesian CNNs using active learning requires up to 35–60 per cent fewer labelled galaxies, depending on the morphological feature being classified. By combining human and machine intelligence, Galaxy zoo will be able to classify surveys of any conceivable scale on a time-scale of weeks, providing massive and detailed morphology catalogues to support research into galaxy evolution.